Case of Endobronchial Needle Aspiration in A Patient With A False COPD Diagnosis - Yaksi, Osman (Archives of Clinical and Biomedical Research, 2017)
Respiratory foreign body aspiration is a critical condition. Foreign body aspirations can be fatal or can rarely be silent. Our case, a 44-year-old female patient diagnosed as COPD at another clinic due to complaints cough and shortness of breath, applied to our service with cough, sputum and shortness of breath. The chest X-ray showed a homogeneous opacity in the lower right section. The foreign body taken out by flexible bronchoscopy and forceps was a needle. It should be noted that foreign body aspiration in adult patients may mimic diseases which cause airway obstruction.